G233(P) The Smartphone Generation. (7th April 2014) - Whitehouse, A; Griffiths, B; Prince, N; Round, J; Kelly, C; Lee, HM
Abstract : Background: We live in a world where the majority of the population carry effectively a small computer around in their pocket, the "Smartphone". We sought to explore just how much smartphones are used in the clinical setting and whether their use is aiding or hindering clinical care. Methods: A questionnaire was disseminated to doctors within the London Deanery via survey monkey. It was sent to doctors at all levels of training including consultants. The data was then analysed including free text responses. Results: We received 210 responses, the responders varied from ST1 to consultants. 95% of those that responded owned a smartphone and the majority of these owned an iPhone. 83% used their smartphone to access clinical resources. When faced with a clinical query 91% would look for answers on a we page and 45% would use a clinical app. The free text responses gave us great insight into the use of smartphones. Discussion: It is clear from our survey that Smartphones are an integral part of many trainees lives. There is great potential to revolutionise the way we approach learning and clinical practice with the aid of apps and smartphone technology. There are drawbacks, such as ensuring the reliability of the apps we use and the issue of governance and patient confidentiality. The "Smartphone Generation" is clearly here and smartphones are a growing integral part of paediatricians lives both clinically and academically. We need to embrace this technology and use it to its full potential to improve our patient care and our own development as Paediatricians.